Climate change and water availability in Indian agriculture: Impacts and adaptation - PATHAK, H; PRAMANIK, P; KHANNA, M; KUMAR, A (The Indian Journal of Agricultural Sciences, 2014)
Climate is a very decisive factor in water resource availability of a region. Warming of the climate system in recent decades is evident from increase in global average air and ocean temperatures, widespread melting of snow and ice, and rising global sea level. The hydrological cycle is intimately linked with changes in atmospheric temperature and radiation balance. A warmer climate may lead to intensification of the hydrological cycle, resulting in higher rates of evaporation and increase of liquid precipitation. These processes, in association with a shifting pattern of precipitation, may affect the spatial and temporal distribution of runoff, soil moisture, groundwater reserves etc. and may increase the frequency of droughts and floods. Agricultural demand, particularly for irrigation water is considered more sensitive to climate change. A change in field-level climate may alter the need and timing of irrigation. Increased dryness may lead to increased demand, but demand may be reduced if soil moisture content rises at critical times of the year. It is projected that most irrigated areas in India would require more water around 2025 and global net irrigation requirements would increase relative to the situation without climate change by 3.5–5% by 2025, and 6–8% by 2075. The effect of climate change on water resources may be mitigated through better water harvesting through the creation of micro-storage facilities in watersheds. These would not only provide supplemental irrigation but also recharge the groundwater aquifers.